(untitled) (GEON Journal (Management, Organizations and Business), 2015)
Disinfection of water and food like fruits and vegetables has been a very important health care factor due to foodborne (ETAS) and water-borne diseases transmitted diseases. This research identified the methods used for water disinfection, fruit and vegetables between housewives and knows the level of acceptance and perception of the study segment against a new natural disinfectant that eliminates 99, 99% of bacteria and pathogens. It was found that is not a habit to use disinfectant for water, fruits and vegetables, however if high interest in the intention of purchasing the study product.